Clinical and Genetic Heterogeneity of CARD14 Mutations in Psoriatic Skin Disease - Israel, Laura; Mellett, Mark (Frontiers in Immunology, 2018)
The CARD: BCL10: MALT1 (CBM) complex is an essential signalling node for maintaining both innate and adaptive immune responses. CBM complex components have gained considerable interest due to the dramatic effects of associated mutations in causing severe lymphomas, immunodeficiencies, carcinomas and inflammatory disease. While MALT1 and BCL10 are ubiquitous proteins, the CARD-containing proteins differ in their tissue expression. CARD14 is primarily expressed in keratinocytes. The CARD14-BCL10-MALT1 complex is activated by upstream pathogen-associated molecular pattern-recognition in vitro, highlighting a potentially crucial role in innate immune defence at the epidermal barrier. Recent findings have demonstrated how CARD14 orchestrates activation of the NF-κB and MAPK signalling pathways via recruitment of BCL10 and MALT1, leading to the upregulation of pro-inflammatory genes encoding IL-36γ, IL-8, Ccl20 and anti-microbial peptides. Following the identification of CARD14 gain-of function mutations as responsible for the psoriasis susceptibility locus PSORS2, the past years have witnessed a large volume of case reports and association studies describing CARD14 variants as causal or predisposing to a wide range of inflammatory skin disorders. Recent publications of mouse models also helped to better understand the physiological contribution of CARD14 to psoriasis pathogenesis. In this review, we summarize the clinical, genetic and functional aspects of human and murine CARD14 mutations and their contribution to psoriatic disease pathogenesis.